2017
DOI: 10.1063/1.4983014
|View full text |Cite
|
Sign up to set email alerts
|

MHD biconvective flow of Powell Eyring nanofluid over stretched surface

Abstract: The present work is focused on behavioral characteristics of gyrotactic microorganisms to describe their role in heat and mass transfer in the presence of magnetohydrodynamic (MHD) forces in Powell-Eyring nanofluids. Implications concerning stretching sheet with respect to velocity, temperature, nanoparticle concentration and motile microorganism density were explored to highlight influential parameters. Aim of utilizing microorganisms was primarily to stabilize the nanoparticle suspension due to bioconvection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…The continuity, momentum, energy, mass and microorganism equations are given by Waqas et al [1][2] and Naseem et al [3]…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The continuity, momentum, energy, mass and microorganism equations are given by Waqas et al [1][2] and Naseem et al [3]…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Different types of sheets were being considered. To illustrate the characteristics of mass and heat movement of gyrotactic microorganisms, Naseem et al [4] observed the bio convective nature of Powell Eyring nanofluid in the influence of MHD forces over the stretched surface. The characteristic of Powell-Eyring fluid is examined by Rosca and Pop [5] with the help of bvp4c function of Mat lab.…”
Section: Introductionmentioning
confidence: 99%
“…First-order homogeneous chemical reaction term is also taken into account. Numerical and graphical results of the considered problems are solved via a homotopy analysis technique [52][53][54][55][56][57][58][59][60][61][62]. Wall drag coefficient and relevant flux rates are arranged and talked about for dimensionless rising parameters.…”
Section: Introductionmentioning
confidence: 99%